Development of Islamic Education Curriculum: Conceptual Study of Thematic Qur'anic Interpretation Perspectives - Muhammad Ghafar (Qolamuna : Jurnal Studi Islam, 2021)
Abstract This article describes the curriculum in Islamic education with the results of the analysis of the study, which concludes first, the content of the curriculum is oriented to "God". Formulation of curriculum content related to divinity, knowing His essence, nature, deeds, and relation to humans and the universe. Second, the content of the curriculum is oriented to "humanity". Formulation of curriculum content related to human behaviour, both humans as individual beings, social beings, cultural beings and intelligent beings. Third, the content of the curriculum is oriented to "nature"—formulation of curriculum content related to the phenomena of the universe as mandated creatures and humans' benefit. Keywords: Thematic Interpretation, Curriculum, Islamic Education